A Critical Analysis of India’s Disaster Management Framework: Addressing Gaps and Enhancing Financial Resource Management - Abhishek Ranjan Bhardwaj (European Economic Letters (EEL), 2024)
India is a nation with diverse eco-geological, socioeconomic, and hazard-prone environments, as evidenced by past disasters and their governance. This research paper provides a critical analysis of India's disaster management framework, with an emphasis on identifying key gaps and enhancing financial resource management. Using a doctrinal approach, the research incorporates a thorough review of relevant legislation and case laws. The findings suggest incorporating disaster risk reduction measures into the legal framework. Several recommendations are made to strengthen India's disaster management laws based on the findings of this study. These include enhancing inter-agency coordination, clarifying roles and responsibilities at all levels of government, empowering local communities in disaster decision-making, increasing investment in disaster risk reduction, and incorporating adaptation strategies to climate change into disaster planning. The paper emphasizes the significance of a flexible and comprehensive legal framework for disaster management in India. By addressing identified gaps and incorporating suggested improvements, particularly in the management of financial resources, India can strengthen its disaster resilience, safeguard lives and livelihoods, and mitigate the far-reaching effects of disasters.